1992
DOI: 10.1177/004051759206200607
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure of Cotton Fabrics Crosslinked with Formaldehyde-Free Reagents

Abstract: Pore structures of cotton fabric crosslinked with several formaldehyde-free durable press reagents are elucidated, and results are compared with those for the industry standard, DMDHEU (dimethyloldihydroxyethyleneurea). The formaldehyde-free reagents were BTCA (butanetetracarboxylic acid), DHDMI (dihydroxydimethylimidazolidinone), and the glyoxal/glycol system; the fabric was an 80 × 80 cotton print-cloth. Treatments were designed to impart the same degree of conditioned wrinkle recovery (WRA) to the fabric. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Crosslinking in cellulosic fibres commonly reduces dye uptake by reducing accessibility of the dye through restricting the movement of the cellulose chains in the non-crystalline regions of the fibres. Three features of crosslinking on cellulosic fibres have been highlighted [18][19][20] in determining properties: primary valence bonds -the covalent bonds formed between the crosslinking agent and the cellulose chains; secondary valence bonds -hydrogen bonding, which are capable of disruption by water and certain swelling agents and of reformation on drying; and the location of the bonds. In contrast, Tencel A100, on which the crosslinking treatment is applied in its wet state, is reported to have an open fibre structure, which leads to higher water retention than standard Tencel, increasing dye accessibility and allowing higher dye uptake and thus higher fixation during reactive dyeing [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Crosslinking in cellulosic fibres commonly reduces dye uptake by reducing accessibility of the dye through restricting the movement of the cellulose chains in the non-crystalline regions of the fibres. Three features of crosslinking on cellulosic fibres have been highlighted [18][19][20] in determining properties: primary valence bonds -the covalent bonds formed between the crosslinking agent and the cellulose chains; secondary valence bonds -hydrogen bonding, which are capable of disruption by water and certain swelling agents and of reformation on drying; and the location of the bonds. In contrast, Tencel A100, on which the crosslinking treatment is applied in its wet state, is reported to have an open fibre structure, which leads to higher water retention than standard Tencel, increasing dye accessibility and allowing higher dye uptake and thus higher fixation during reactive dyeing [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Apparently the two adjacent carboxylic acid groups dehydrate and form a five-membered cyclic anhydride intermediate, which may further react with a hydroxyl group of cellulose via esterification (Bertoniere and King 1992;Wing 1997;Yang and Wang 2000). Accordingly the maximum number of ester bonds is one less than the total number of carboxylic groups in the reactant (Bertoniere and King 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Those phenomena strongly suggested that the pore structure caused by the crosslinking of DMDHEU–α‐amino acid might be different from that for DMDHEU alone. Many other authors5–8 mentioned that the pore structures of the treated fabrics are affected by varying the functional groups of crosslinking agents. We are interested in the effect of the coreactants of the α‐amino acids having one carboxylic acid group and one amine group on the pore structure of the treated fabrics, which has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM pictures will also be used to confirm the state of the pore structures of DMDHEU and DMDHEU–α‐amino acids‐treated fibers. On the other hand, a negative staining method described by Rowland et al8, 13, 14 will be used to determine the distribution of agents on the treated fabrics.…”
Section: Introductionmentioning
confidence: 99%